Triumph through texting: Restoring learners' interest in grammar. Issue 3 (29th June 2017) - Hedjazi Moghari, Mona; Marandi, S. Susan
Abstract: It is usually the case that learners of English as a foreign language (EFL) are exposed to language materials in class only, and of course in such a short space of time, they do not always find enough chance to practice English grammar features and become aware of their grammar mistakes. As a potential solution to this problem, the current study inspects the impact of using cell phones, specifically text messages (via short message service) as supplementary tools, on Iranian elementary level EFL learners' grammar learning. In the first phase of the study, 60 students aged 14 were randomly divided into experimental and comparison groups. Throughout the 12 weeks of treatment, the participants in the experimental group received 120 text messages containing grammar exercises, whereas the participants in the comparison group received a similar number of vocabulary messages as a placebo treatment and were otherwise treated exactly the same as the experimental group. A researcher-made grammar test was used to estimate whether presenting grammar exercises via text messages has any impact on language learners' grammar learning. The results demonstrated that there was a significant difference (p<0.05) in the grammar learning of the participants who practiced grammar points through text messages and those who did not. The researchers also interviewed various stakeholders, comprising ten students, five parents, the teacher, and the school principal. A qualitative content analysis was carried out to find themes relevant to the stakeholders' beliefs about making use of text messages for learning grammar. The findings suggest that text messages can be useful for learning grammar points, since they engage learners' interest and encourage them to study more in order to text the correct answers when they are outside their classrooms.